2018
DOI: 10.1016/j.jot.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Update on biomaterials for prevention of epidural adhesion after lumbar laminectomy

Abstract: SummaryLumbar laminectomy often results in failed back surgery syndrome. Most scholars support the three-dimensional theory of adhesion: Fibrosis surrounding the epidural tissues is based on the injured sacrospinalis behind, fibrous rings and posterior longitudinal ligaments. Approaches including using the minimally invasive technique, drugs, biomaterial and nonbiomaterial barriers to prevent the postoperative epidural adhesion were intensively investigated. Nevertheless, the results are far from satisfactory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 50 publications
0
45
0
3
Order By: Relevance
“…Adhesion in epidural tissue is caused by the propagation of fibroblasts and fibroblast‐producing collagen fibers, with the fibroblasts originating from the injured sacrospinalis, intervertebral disc fibers, fiber ring, and posterior longitudinal ligament . Because fibroblast adhesion and the combined cellular response contribute to various aspects of wound healing, many studies have been conducted to clarify the adhesion mechanism of fibroblasts in these tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion in epidural tissue is caused by the propagation of fibroblasts and fibroblast‐producing collagen fibers, with the fibroblasts originating from the injured sacrospinalis, intervertebral disc fibers, fiber ring, and posterior longitudinal ligament . Because fibroblast adhesion and the combined cellular response contribute to various aspects of wound healing, many studies have been conducted to clarify the adhesion mechanism of fibroblasts in these tissues.…”
mentioning
confidence: 99%
“…Adhesion in epidural tissue is caused by the propagation of fibroblasts and fibroblast-producing collagen fibers, with the fibroblasts originating from the injured sacrospinalis, intervertebral disc fibers, fiber ring, and posterior longitudinal ligament. 9,10 Because fibroblast adhesion and the combined cellular response contribute to various aspects of wound healing, 3,11 many studies have been conducted to clarify the adhesion mechanism of fibroblasts in these tissues. Mechanisms including enhanced collagen synthesis by fibroblasts that migrated from paraspinal muscles, inflammation triggered by intervertebral disc fibroblasts, and activated interleukin-6 expression due to angiopoietin-like protein 2 binding in ligamentum flavum fibroblasts have been proposed.…”
mentioning
confidence: 99%
“…1,2 In some cases, recovery is achieved by light scale medical intervention or minimally invasive methods, but in some cases postoperative back pain is not relieved, even with interventions such as complex surgeries. 1,[3][4][5] Failed back surgery syndrome is characterized by recurrent continued pain after neurosurgical intervention such as lumbar laminectomy, and has gained the attention from spinal surgeons. [5][6][7] Epidural fibrosis is a natural outcome of laminectomy, being the formation of excessive scar tissue at the surgical site.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,8 The literature has already reported that scars may cause clinically significant sequalae by creating adherences in between the tissues, or as a result of the dense fibrous tissue exerting pressure on the surrounding anatomical structures. [1][2][3][4][5][6][7][8][9] Although there is no consensus on the PRP was prepared by obtaining 10 cc blood from a rat in the donation group and put into tubes with citrate phosphonate dextrose (CPD). Additional 0.5 cc blood put into pediatric tubes with EDTA and sent to the autoanalyzer for cell count;10 cc blood with citrate were transported to the hematology laboratory in the cold chain for the preparation of PRP.…”
Section: Introductionmentioning
confidence: 99%
“…and synthetic polymers (PLGA, ePTFE, etc. ), in use alone or combination with drugs and other agents . Although acquiring good short‐term clinical outcomes, the long‐term effectiveness and safety of the above implants need further confirmation.…”
Section: Introductionmentioning
confidence: 99%